2012
DOI: 10.3109/09537104.2012.721907
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin: Anti-platelet effect in diabetes and healthy volunteers

Abstract: Sitagliptin, a selective dipeptidyl peptidase-4 inhibitor drug is used to treat type-2 diabetes (T2DM). We investigated the anti-platelet activity of sitagliptin in patients with T2DM and in in vitro samples obtained from healthy humans. Patients with T2DM (27 male + 23 female) were selected and followed up before (control) and after treatment with sitagliptin for up to 3 months. Platelets were isolated from the blood of sitagliptin treated patients and controls. Patients with T2DM treated with sitagliptin for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 38 publications
1
37
1
1
Order By: Relevance
“…Given that there should have been no GLP-1 present in their platelet preparations, and that we have been unable to document any DPP-4 activity in platelets (or MEG-01 cells) (Supplementary Fig. 3), the results of Gupta et al (17) are somewhat surprising. We can only speculate as to whether their results in vitro suggest a "direct" action of sitagliptin on platelet biology (i.e., independent of GLP-1 or DPP-4).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Given that there should have been no GLP-1 present in their platelet preparations, and that we have been unable to document any DPP-4 activity in platelets (or MEG-01 cells) (Supplementary Fig. 3), the results of Gupta et al (17) are somewhat surprising. We can only speculate as to whether their results in vitro suggest a "direct" action of sitagliptin on platelet biology (i.e., independent of GLP-1 or DPP-4).…”
Section: Discussionmentioning
confidence: 64%
“…Because the rather modest and brief improvements in glycemic control observed in these studies are unlikely to explain the observed benefits, we wondered whether GLP-1-targeted therapies may reduce macrovascular event rates in these particular patient populations by directly inhibiting platelet aggregation and thrombus formation. Indeed, this premise could be extrapolated from the one small uncontrolled study (17) that demonstrated the curious ability of DPP-4i sitagliptin to inhibit thrombin-induced platelet aggregation in vitro.…”
mentioning
confidence: 99%
“…Thus, DPP-IV itself may be important to the pathogenesis of NASH. Use of the DPP-IV inhibitor, sitagliptin, improves lipid metabolism, and attenuates the progression of hepatic fibrosis in mice with NASH, as well as decreases platelet aggregation in vitro [20,21] . Thus, sitagliptin may be an attractive therapeutic option for NASH, especially given its low risk of hypoglycemia, weight-neutrality, and demonstrated safety profile in individuals with moderate hepatic insufficiency [22,23] .…”
Section: Introductionmentioning
confidence: 99%
“…DPP-4 inhibitors are now considered as one of the well-established therapies available for diabetes mellitus type 2 (T2DM): in addition to the well-known anti-hyperglycemic and pancreatic islet protective effects, other effects of novel DPP-4 inhibitors have been observed, such as immune regulation [2][3][4][5], cardiovascular protection [6][7][8][9][10] and anti-inflammatory effects [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%